Pengetahuan, Sikap dan Kesiapan Perawat Klinisi Dalam Implementasi Evidence-Base Practice : Knowledge, Attitude, and Readiness of Clinical Nurses in Implementing Evidence-Based Practice - Titan Ligita; Winarianti; Riduan Novaris (Fakultas Keperawatan Universitas Andalas, 2012)
Nurses have responsibility in providing the best nursing care for their patients. Providing the care is based not only on clinical experiences but also on nursing research findings to explore best nursing interventions for patients in order to obtain optimal outcomes. Through the concept of evidence-based practice, research findings may influence nurses in clinical decision making. Therefore, nurses should know the concept properly and have a positive attitude as well as be prepared in applying evidence-based practice. The aim of this study was to identify knowledge, attitude, and preparation of clinical nurses in the application of the evidence-based practice concept. This study used a cross-sectional design by generating a questionnaire to 66 clinical nurses in a general hospital in Pontianak. The result has shown that nurses’ knowledge on the concept of evidence-based practice was considerably low. Furthermore, they basically had not enough preparations in terms of knowledge and habit in conducting research and reading research findings where these components are very important in supporting the implementation of evidence. However, more than half of the nurses had a positive attitude towards evidence-based practice. The findings in this study are important for nursing education and nursing practice in providing the best practice for the patients.